FIRM RESILIENCE RESEARCH DEVELOPMENT: A BIBLIOMETRIC ANALYSIS WITH VOSVIEWER - Metta Padmalia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research examines the development of research on the topic of firm resilience which is currently very relevant to the conditions of the Covid-19 pandemic using bibliometric analysis with the support of the VOSviewer application. This study aims to find out: (1) the development of research on firm resilience published in international journals listed on the Scopus database from 1991-2021; (2) publication of international journals on corporate resilience; and (3) a map of the development of international research publications in the field of keyword-based firm resilience. Data collection was carried out through a search through the Scopus website with the keyword "firm resilience", with the categories of article titles, abstracts, keywords for the period 1991-2021. Analysis and visualization of database is carried out using the VOSviewer application. As a result, the citation analysis found 17,028 citations from 1991 to 2021. Ivanov, D. is the most productive researcher of the ten publications. A term author keyword trend analysis found that 3,289 author keywords were used in selected articles containing at least 10 events, yielding 38 author keywords with strong relevance. The term "Covid-19" is the term most used by writers with a total of 87 channels of connections. The country that publishes the most articles on corporate woes is the United States, with 303 articles.